CLINICAL CHARACTERISTICS AND SURGICAL OUTCOME OF INCIDENTAL GALL BLADDER CANCERS DURING OR AFTER CHOLECYSTECTOMY (The Research of Medical Science Review, 2025)
Objective: To measure the frequency of incidental gall bladder carcinoma (GBC) during and after cholecystectomy and compare the clinical characteristics and surgical outcomes between both groups. Study design: Quasi-experimental study Place and duration of study: Surgery department of Army Liver Transplant Unit Pak Emirates Military Hospital (PEMH) from July 2023 to July 2024. Methodology: After ethical approval, we collected a sample of 52 patients who were diagnosed with incidental gall bladder cancers during or after cholecystectomy. We studied and compared their clinical characteristics, risk factors and surgical outcomes. Results: Total 10 (19.23%) patients had Isolated Cholecystectomy, and 42(80.76%) patients had radical cholecystectomy. Chronic cholecystitis was found in 7(70.0%) patients in group DDLC and 42(100.0%) patients in DALC with p value 0.005. Acute cholecystitis was found in all patients in group DDLC and 27(64.3) patients in group DALC with p value of 0.002. Conclusion: We concluded that the frequency of incidental gall bladder cancers is higher during histopathology than during laproscopic cholecystectomy and surgical outcomes are affected by this. The demographic characteristics, risk factors and clinical features do not differ significantly from the surgical outcome and mode of diagnosis.